CULTURAL TOURISM AND WELL-BEING OF LOCAL POPULATION IN SIKKIM - Bhutia, Sonam Tshering (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the impact of cultural tourism on the well-being of local populations in Sikkim, India. It highlights the dual nature of cultural tourism, emphasizing both its potential benefits and challenges. Key findings indicate that cultural tourism can enhance residents' well-being through economic opportunities, social cohesion, and the preservation of cultural heritage, exemplified by events like the Losar Festival. However, issues such as over-tourism and cultural commodification pose significant risks. The study emphasizes the importance of sustainable tourism practices, community involvement in planning, and policies that prioritize local interests to ensure equitable benefits. By focusing on local well-being, Sikkim can develop a tourism model that not only attracts visitors but also enriches the lives of its residents, preserving its unique cultural identity for future generations. The findings underscore the necessity of balancing tourism growth with the preservation of cultural heritage and the enhancement of local quality of life.